Stres Kerja Petugas Pendaftaran Rawat Jalan di Rumah Sakit Umum Madani Medan - Zulham Andi Ritonga; Nabilla Dwi Putri Siregar; Siddik Karo Karo (Lembaga Pengembangan Kinerja Dosen, 2026)
Occupational stress is a physical or psychological reaction that occurs when job demands are unbalanced with an individual's ability to cope. This condition is often experienced by outpatient registration officers who are required to provide fast, accurate service, and deal with a fluctuating number of patients every day. This study aims to determine the factors influencing occupational stress among outpatient registration officers at Madani General Hospital, Medan, in 2025. This study used a qualitative approach with in-depth interviews with five informants, as well as direct observation to strengthen the findings in the field. The results showed that occupational stress is influenced by several factors, namely the work environment (cleanliness and noise), workload (number of patients and demands from patients' families), superior support (direct interaction with superiors and assistance during difficulties), working hours (regularity of working hours and availability of rest periods), and salary (relationship with work enthusiasm and motivation). An unclean and noisy work environment due to building renovations was the main trigger for discomfort. In addition, the increased workload on certain days and high demands from patients and families added to psychological stress. Although some officers felt supported by their superiors and received adequate rest periods, aspects of work well-being were still considered suboptimal. Researchers concluded that work stress among outpatient registration staff is a complex problem influenced by both environmental and organizational factors. Hospital management needs to take strategic steps to improve the work environment, manage a balanced workload, and provide motivation and recognition to staff to improve mental well-being and the quality of healthcare services.